Wavy Wind-Water Flow Impacts on Offshore Wind Turbine Foundations - Rehil Thomas; Odeh Dababneh; Mustapha Gourma (Journal of Marine Science and Engineering)
The present study investigates the flow dynamics surrounding offshore wind turbine OWT foundations, focusing on the interaction of wind and water flows with two prevalent foundation types: mono-pile and tripod designs. Computational simulations and analyses were conducted on the substructures of these OWTs using the ANSYS-Fluent v16.5 software package. The primary objective was to predict critical parameters, including directional drag force coefficients, interface velocities, and pressure distributions. To model realistic oceanic conditions, pseudo-periodic wave patterns were implemented at the inlet boundary. The flow regime was characterized by logarithmic vertical velocity profiles at low interfacial velocities, ranging from 2.23 m/s to 3.01 m/s. This computational approach revealed anisotropic constraints imposed on the foundations under unidirectional flow conditions. The drag coefficients obtained from the simulations highlighted significant vertical flux exchanges in proximity to the OWT structures, with a particularly pronounced downward flow near the tripod foundation design. Additionally, the study demonstrated that variations in wind speed within the specified range did not substantially impact pressure distributions or strain rates. However, these changes were found to influence skin friction coefficients, indicating a sensitivity of these hydrodynamic parameters to wind speed variations. The analysis of flow streamlines around the mono-pile foundation showed a smooth and well-defined pattern, whereas the flow around the tripod foundation exhibited more complex, interleaved, and turbulent streamlines. This distinction in flow behavior is believed to contribute to the observed downward vertical flux exchanges near the tripod.